(untitled) (Applied Biological Research, 2017)
Grains of fifty lines of bread wheat (Triticum aestivum L.) representing diverse genotypes were analyzed in the year 2015 for variation in their micronutrient concentrations. Both grain Zn and Fe concentrations correlated negatively with grain yield and 1000-grain weight. Zn concentration also correlated significantly but negatively with phenol reaction score and plant height. Grain Fe concentration correlated significantly but positively with plant height, grain Zn and grain protein concentration. However, the correlations of Fe content with days to heading, grain appearance score, sodium dodecyl sulphate (SDS) sedimentation value and phenol reaction score and correlations of Zn content with days to heading, grain appearance score, SDS and grain protein were weak. Both Fe and Zn concentration showed negative direct on grain yield. Significant differences between bread wheat genotypes were found for grain Fe and Zn concentrations. Five entries namely 448, 412, 420, 414 and 419 showed high values for both Fe and Zn concentration. For Zn, an increment of 33.3% (54.4 ppm) over check (40.8 ppm) was observed. For Fe, an increment of 28.1% (45.1 ppm) was observed over check (35.2 ppm). The information generated could be used for developing micronutrient biofortification strategies.